Traduire l’histoire : entre paroles et images - Castro-Ramirez, Nayelli; Wiater, Aleksander (Studia Romanica Posnaniensia, 2021)
In an age when the global dissemination of digital information is transforming the way we read and write by foregrounding the interdependence of visual/verbal elements and languages, the reconstruction of identity and history in digital environments challenges binary translation processes. From this perspective, we interrogate the integration of visual and verbal elements in three Wikipedia articles, written in Polish, English, and Portuguese, about the topic “Polish death camp”. What is the role of translation in the semiotic construction of historical discourses in these articles? What are the conflicts generated by translated denominations? How do Wikipedia communities engage with the production of these cognitive representations? This paper attempts to answer these questions.